Innovative work behaviour under participative leadership among 2 high performance work culture companies in Malaysia / Lee Hywe Theng - Lee, Hywe Theng (2012)
Many studies have investigated the main determinants of employees’ Innovative Work Behaviour (IWB) which includes personal traits, individual competencies or skills, the reward system, income and incentives, the quality of relationships between coworkers and team composition, as well as job characteristics are found to be regarded as an important antecedents of IWB. On top of the above-mentioned factors, company work culture is also one of the important linking elements for IWB. It is defined as how employees view their work culture and how they perceive leadership support for innovation is more important than the company’s objective and definition of innovation is. The purpose of this study is to investigate the effect of participative leadership in employees’ innovation work behaviour between two high performance Work Culture Companies – IBM and HP Malaysia. In order to meet the finding purpose, a questionnaire surveys was conducted for this study. There is a total of 205 complete questionnaires collected. All respondents were picked from the Operational department of both IBM Sdn. Bhd. and HP Sdn. Bhd. to make a comparison between employees/respondents of the same working background. Results of the survey demonstrated that high performance work culture and participative leadership in an organization has positive relationship with employee’s innovation work behaviour and innovative output.